Civic Character in The Post-Truth Era: Reassessing Thomas Lickona’s Character Education Theory in Digital Space - Ryan Taufika; Karim Suryadi; Cecep Darmawan; Asep Mahfudz (Lembaga Bale Literasi, 2026)
This article critically reassesses the relevance of Thomas Lickona's character education theory in explaining civic character within the post-truth digital environment. As digital platforms increasingly shape how citizens access information, form opinions, and engage in public life, civic character is no longer formed solely through traditional institutions but through algorithmically mediated, affective, and epistemically unstable environments. A significant research gap exists in that prior applications of Lickona's framework have not adequately examined its explanatory adequacy in post-truth digital contexts, nor proposed systematic reconstructions grounded in digital civic theory. Using qualitative library research and critical-conceptual analysis, this study examined scholarly literature across civic education, media studies, and digital political communication. Data were collected through purposive literature selection and analyzed through four interrelated stages: conceptual identification, thematic comparison, critical interpretation, and conceptual reconstruction. Conceptual triangulation was employed to enhance analytical rigor. The analysis finds that Lickona's triadic model moral knowing, moral feeling, and moral action remains normatively valuable as an ethical foundation for civic character, particularly in fostering civic discernment, empathy, and responsibility. However, the theory is analytically insufficient for addressing the socio-technical realities of post-truth citizenship, including algorithmic mediation, affective virality, and epistemic instability. This article proposes a reconstructed framework of digital civic character that extends Lickona's theory through (1) critical digital discernment, (2) digital civic empathy, (3) responsible digital civic engagement, and (4) algorithmic awareness. The study contributes to the theoretical renewal of character education for democratic life in digital society.